VIDEO-SURVEILLANCE OF URBAN SPACE: TRAFFIC, SECURITY AND SOCIAL CONTROL (Andamios, Revista de Investigación Social, 2010)
In recent years, in Mexico and globally, closed circuit television (CCTV) has become the most pervasive surveillance model for urban spaces to record the daily activities of people. CCTV is not only a divices to support policies on security, organization of traffic, but instrument of social and political control. Taking the case of two municipalities in Mexico, this paper analyzes how these surveillance technologies allowing a certain management of the city as well as different forms of governmentality of population.
Keywords: Surveillance; guvernmentality; social control; social care; surveillance technologies